PEMANFAATAN ANALISIS BREAK EVENT POINT DALAM PERENCANAAN LABA (STUDI KASUS PT. SUBUR PAYAKUMBUH) - Angelina Siska Mahardi; Yefni -; Atika Zarefar (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2017)
This research was conducted at PT. Subur Payakumbuh property of Mr. Yohardi is located at Jalan Tan Malaka No. 174 Parit Lampung Payakumbuh. The purpose of this research is to analyze break event point (BEP) in profit planning (case study of PT Subur Payakumbuh). Data collection techniques is by interview, observation and documentation. Source of data obtained from owner of the  PT. Subur Payakumbuh and type of data used are primary data and secondary data. The result of calculation of BEP (unit) obtained is as much as 36.766.030 eggs and BEP (Rupiah) obtained is as much as Rp34.874.805.341. After obtained BEP calculation, the management of PT. Subur Payakumbuh can use several alternatives for profit planning in 2017. The first alternative that can be done is to reduce costs or minimize existing costs. The second alternative is by increasing the sales volume from 41,117,363 eggs to 42,163,609 eggs. The third alternative that can be done by PT. Subur Payakumbuh as a tool of management by increasing the average selling price of eggs from Rp948,561 to Rp1.054.